Tribal journey - Robinson, Gary, 1950- (7th Generation, 2013)
Sixteen-year-old Jason is left with a paralyzed leg after a car accident and it is only after becoming involved with his Duwamish mother's tribe and learning to "pull" a canoe that he begins to see himself as more than a boy in a wheelchair.